Relationship between high work intensity, organisational performance and workers' health - Kohont, Andrej (Teorija in praksa, 2019)
The aim of the study is to examine the relationship between work intensity, organisational performance and worker health in Slovenia. One finding is that organisations with a lower work intensity are more focused on (the needs of) their employees and more financially successful. Yet, greater work intensity significantly deteriorates workers' health. The results confirm the need for an appropriate distribution of workloads, and a properly designed working environment that strengthens individual involvement in work results while contributing to employees' better health.
Keywords: Delo; delovna storilnost; Employees; Health; Organizacije; Organizations; Work; Zaposleni; Zdravje